ENERGY SAVING MANAGEMENT WITH SUGGESTION METHOD HOME AUTOMATION BASED ON USER HABITS - Fahmi Nurfadilah, Muhammad
The need for electrical energy is the main thing in everyday life, especially the housing sector. Electricity consumption is very useful for everyday life such as lighting a room, turning on a water pump, and some household appliances that require electricity. With the variety of electricity use in households, it is directly proportional to the increase in electricity consumption needed, especially if the use of electricity is full of energy generation. Because electricity consumption continues to increase, the electricity supply provided will also continue to increase and even be erratic. The need for electricity is a serious problem, because it will be in direct contact with the preservation of nature. Most of the electricity supply requires natural resources of coal as raw material for processing electricity which is then developed into houses for electricity needs. With the increase in demand, of course, it will be directly proportional to the production that must be prepared, causing the need for coal to increase which can result in environmental damage, especially the erosion of soil which is a natural resource. For this reason, it is necessary to take simple steps to save electrical energy, so that the use of electricity in the household can be used properly and not excessively. Electrical energy savings can be done simply by using instrumentation devices that can set when to turn on and off automatically as needed. An instrumentation device becomes an integrated system between household appliances with an internet connection which we usually know as IoT (Internet of Things). The IoT instrumentation device will be combined with the suggestion method of using electricity for scheduling, which will become an automation system used to control and monitor household appliances which can then be called Home Automation.